Patologia dos neoplamas malignos orais em cães - Aguiar, Ariel de (2022)
This study aimed to characterize the cases of malignant neoplasms of the oral cavity of dogs from approximately 23 years of routine diagnosis at the Laboratory of Veterinary Pathology (LPV) of the Federal University of Santa Maria (UFSM). Through these data, two scientific articles were prepared that make up this dissertation. The first article is an overview of malignant neoplasms of the oral cavity, collecting data such as sex, race, age, clinical signs, neoplasm location, macroscopy and histology. During the study period, 205 dogs were affected by oral neoplasms, of which 101 were malignant. Of these, 47 were melanomas, 19 fibrosarcomas, 17 squamous cell carcinomas. Other less prevalent malignant neoplasms included undifferentiated sarcoma, mast cell tumor, hemangiosarcoma, osteosarcoma, transmissible venereal tumor, chondrosarcoma, and acinar cell carcinoma of the salivary gland. 51 cases were observed in females and 45 cases in males. Mixed-breed dogs totaled 33 cases and 64 dogs were defined-breed. The age range was from 1 to 19 years. The main clinical signs were swelling in the oral region, dysphagia, oral bleeding and drooling. The most affected sites were the gingiva, oral mucosa, mandible and mucocutaneous junction. Thus, through the two articles of this dissertation, it is possible to establish the frequency of these neoplasms in the studied period, as well as their clinical, macroscopic and histological, histochemical and immunohistochemical characteristics. The second article addresses a total of 47 melanomas in the oral cavity of dogs, in which clinical signs and anatomopathological aspects were characterized and the use of histochemical Toluidine Blue (TA) staining for the evidencing of melanin granules in comparison with the Fontana Masson (FM). In addition, the use of AT as a counterstain for the immunohistochemistry technique was evaluated. The clinical sign most frequently observed in dogs with oral melanoma was swelling in the oral region. The main site of involvement was gingiva (27.65%), followed by oral mucosa (21.27%) and mucocutaneous junction (12.76%), among others. Tumors were described as ulcerated nodules or masses, mostly between 0.5 and 2.0 cm in diameter. Histologically, the subtypes observed were epithelioid (44.6%), fusiform (27.6%), mixed epithelioid and fusiform (14.8%), ballooning (4.2%), small cells (4.25%), myxoid (2.12%) and round cells (2.12%). The histochemical techniques for quantification of melanin granules did not show differences between FM and AT. TA showed melanin granules as green to dark green dots or aggregates. Sections counterstained with AT and Harris' hematoxylin allowed a clear distinction between melanin (stained green) and immunostaining for Melan-A (stained brown). When the cells were MelanA-positive and had melanin in the cytoplasm, a third color pattern was shown (a mixture of yellow and green).